Exposure to ambient particulate matter affects semen quality: A case study in Wenzhou, China. (27th October 2022) - Dai, Xuchao; Chen, Gang; Zhang, Mengqi; Mei, Kun; Liu, Yanlong; Ding, Cheng; Chang, Yanxiang; Wu, Zhigang; Huang, Hong
Abstract: Background: Particulate matter (PM), including PM2.5 (PM ≤ 2.5 µm in aerodynamic diameter) and PM10 (PM ≤ 10 µm in aerodynamic diameter), is a component of air pollutants, which is linked to semen quality. However, the available evidence of association needs to be strengthened, and some studies have conflicting results. Objectives: To evaluate the potential impacts of PM on semen quality during the full (0–90 days before semen examination) and three key sperm development windows (0–9, 10–14, and 70–90 days before semen examination). Methods: We included 1494 infertile men in the main urban area in Wenzhou, China, who had undergone semen examinations for fertility between 2014 and 2019. The impacts were assessed by multivariable linear regression models. Results: Overall, during the full sperm development window, PM2.5 and PM10 exposures were associated with declined progressive sperm motility (%) (β: −0.6; 95% confidence intervals (CIs): −1.07, −0.13 and −0.46; −0.59, −0.33) and total sperm motility (%) (−1.95; −2.67, −1.23 and −1.32; −1.82, −0.82), and associated with increased sperm concentration (10 6 /ml) (0.02; 0.006, 0.023 and 0.007; 0.001, 0.013) and total sperm number (10 6 ) (0.02; 0.01, 0.03 and 0.011; 0.004, 0.017). Furthermore, only PM2.5 exposure during the 10–14 days window was significantly associated with declined progressive motility (%) (−0.207; −0.395, −0.023). Conclusions: During the full sperm development window, PM exposure has an adverse impact on sperm motility and positive impacts on sperm concentration and total sperm number. The adverse impact was more severe in the 10–14 days window.